Effects of financing smoking cessation outpatient services in Taiwan. Issue 3 (3rd June 2008) - Chang, F-C; Hu, T-W; Lin, M; Yu, P-T; Chao, K-Y
Abstract : Objective: This study assesses the effects of a 2005 increase in funding for smoking cessation services on provider participation, patient utilisation of smoking cessation services and cessation outcome at a six-month follow-up. Methods: Analyses are based on existing databases and on a follow-up study among smokers participating in the smoking cessation service. The effect of the policy is evaluated by comparing year 2004 (old policy) with year 2005 (new policy). The generalised estimating equations (GEE) method was conducted to examine the effects of increasing funding for smoking cessation services on monthly smoking cessation services provided per physician and yearly consultations received per patient. Logistic regression was used to examine the effects of increasing funding on smoking cessation outcome. Results: The study found the increased reimbursement rates and medication subsidies for smoking cessation to be positively related to the number of physicians enrolling in the programme (1841 in 2004 vs 3466 in 2005), the number of cessation consultations per month per physician (5.1 vs 14.6) and the number of cessation visits per year per patient (2.0 vs 2.5). Male providers and providers belonging to the private sector were found to offer more cessation consultations. The number of subjects receiving this counselling increased from 22 167 in 2004 to 109 508 in 2005. After adjusting for consumer and provider factors the likelihood of successful quitting among those counselled did not change. Overall, smokers who were older, had attempted to quit in the past year, had lower nicotine dependence, had gone to more smoking cessation service visits, had received consultations in the public sector and were seen by physicians delivering fewer consultations were more likely to have quit smoking at the six-month follow-up. Conclusions: Based on increases in physician enrolment and consultations and the increase in number of subjects receiving counselling and number of visits, the policy of increasing provider incentives and medication subsidies appears to have successfully promoted smoking cessation services.